The Morals behind Restraining Rights and Freedoms: A Classical Overview (Sambahak: Human Rights Journal, 2025)
The main purpose of the analysis is to explore the evolutionary trends of the restraint to freedoms by both state and non-state actors. An effort is made whether the restraints were morally sound even during the absence of written law in the history and prehistory. This product is an outcome of historical research mainly based on doctrinal work. In writers view morality has been the principal steward to make fair restraints upon various form of freedoms.  In the course different groups of elites imposed excessive restraints upon freedom to fellow human. Much of those restraints were directed to capture the wealth, power and serve the interest of ruling elites. The humanistic approach to rights and freedoms of the native communities sidelined with the reception of rights and freedoms evolved in the foreign soil. The Hindu and Buddhist scriptures witness the fact of suppression either in explicit or implicit form. The methods of spirituality and meditation to purify inner self that would prevent or make self-restraint of rights abuses were outlawed. The restraints are always expected to be fair, reasonable, ethical and moral in the eye of public. Proper scrutiny measures should be put in place to make surveillance upon restriction made against rights and freedoms. The struggles for freedoms are ever going and probably never ending and therefore that rest on the highest echelon of human mind. Its preciousness is not comparable and therefore humankind deserves any power to defend for freedom.  The cost of freedom is immeasurable and also of its fair restraints.